kidzsearch.com > wiki   Explore: web images videos games

# Mathematical induction

Mathematical induction is a special way of proving a mathematical truth. It can be used to prove that something is true for all the natural numbers (or all positive numbers from a point onwards). The idea is that if:

1. Something is true for the first case (base case);
2. Whenever that same thing is true for a case, it will be true for the next case (inductive case),

then

• That same thing is true for every case by induction.

In the careful language of mathematics, a proof by induction often proceeds as follows:

• State that the proof will be by induction over $n$. ($n$ is the induction variable.)
• Show that the statement is true when $n$ is 1.
• Assume that the statement is true for any natural number $n$. (This is called the induction step.)
• Show then that the statement is true for the next number, $n+1$.

Because it is true for 1, then it is true for 1+1 (=2, by the induction step), then it is true for 2+1 (=3), then it is true for 3+1 (=4), and so on.

An example of proof by induction is the following:

Prove that for all natural numbers n:

$1+2+3+....+(n-1)+n=\tfrac12 n(n+1)$

Proof:

First, the statement can be written as:

$2\sum_{k=1}^n k=n(n+1)$ (for all natural numbers n)

By induction on n,

First, for n=1:

$2\sum_{k=1}^1 k=2(1)=1(1+1)$,

so this is true.

Next, assume that for some n=n0 the statement is true. That is,:

$2\sum_{k=1}^{n_0} k = n_0(n_0+1)$

Then for n=n0+1:

$2\sum_{k=1}^{{n_0}+1} k$

can be rewritten as

$2\left( \sum_{k=1}^{n_0} k+(n_0+1) \right)$

Since $2\sum_{k=1}^{n_0} k = n_0(n_0+1),$

$2\sum_{k=1}^{n_0+1} k = n_0(n_0+1)+2(n_0+1) =(n_0+1)(n_0+2)$

Hence the proof is complete by induction.

## Similar proofs

Mathematical induction is often stated with the starting value 0 (rather than 1). In fact, it will work just as well with a variety of starting values. Here is an example when the starting value is 3: "The sum of the interior angles of a $n$-sided polygon is $(n-2)180$ degrees."

The initial starting value is 3, and the interior angles of a triangle is $(3-2)180$ degrees. Assume that the interior angles of a $n$-sided polygon is $(n-2)180$ degrees. Add on a triangle which makes the figure a $n+1$-sided polygon, and that increases the count of the angles by 180 degrees $(n-2)180+180=(n+1-2)180$ degrees. Since both the base case and the inductive case are handled, the proof is now complete.

There are a great many mathematical objects for which proofs by mathematical induction works. The technical term is a well-ordered set.

## Inductive definition

The same idea can work to define a set of objects, as well as to prove statements about that set of objects.

For example, we can define $n$th degree cousin as follows:

• A $1$st degree cousin is the child of a parent's sibling.
• A $n+1$st degree cousin is the child of a parent's $n$th degree cousin.

There is a set of axioms for the arithmetic of the natural numbers which is based on mathematical induction. This is called "Peano's Axioms". The undefined symbols are | and =. The axioms are

• | is a natural number.
• If $n$ is a natural number, then $n|$ is a natural number.
• If $n| = m|$ then $n = m$.

One can then define the operations of addition and multiplication and so on by mathematical induction. For example:

• $m + | = m|$
• $m + n| = (m + n)|$